Gut microbiota dysbiosis as an inflammaging condition that regulates obesity-related retinopathy and nephropathy - Li, Jie; Lv, Jun-lin; Cao, Xin-yue; Zhang, Hai-ping; Tan, Yu-jun; Chu, Ting; Zhao, Li-li; Liu, Zhong; Ren, Yu-shan (Frontiers in Microbiology, 2022)
Diabetes-specific microvascular disease is a leading cause of blindness, renal failure and nerve damage. Epidemiological data demonstrated that the high morbidity of T2DM occurs as a result of obesity and gradually develops into serious complications. To date, the mechanisms that underlie this observation are still ill-defined. In view of the effect of obesity on the gut microflora, Leprdb/db mice underwent antibiotic treatment and microbiota transplants to modify the gut microbiome to investigate whether microbes are involved in the development of diabetic nephropathy and/or diabetic retinopathy. The mouse feces were collected for bacterial 16S ribosomal RNA gene sequencing. Cytokines including TNF-α, TGF-β1, IFN-γ, IL-1β, IL-6, IL-17A, IL-10 and VEGFA were detected by ELISA, flow cytometry, real-time PCR and immunofluorescent assay. Eyes and kidney were collected for histopathological assay. Intestinal permeability was also detected using Evans Blue. The results showed that obesity influenced metabolic variables (including fast/fed glucose, insulin, and triglyceride), retinopathy and nephropathy, and the gut microbiota. Obesity mainly reduced the ratio of Bacteroidetes/Firmicutes and influenced relative abundance of Proteobacteria, Actinobacteria, and Spirochaetes. Obesity also increased intestinal permeability, metabolic endotoxemia, cytokines, and VEGFA. Microbiota transplants confirm that obesity aggravates retinopathy and nephropathy through the gut microbiota. These findings suggest that obesity exacerbates retinopathy and nephropathy by inducing gut microbiota dysbiosis, which further enhanced intestinal permeability and chronic low-grade inflammation.